2022
DOI: 10.1001/jamanetworkopen.2021.42773
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With 10-Year Declines in Physical Health and Function Among Women During Midlife

Abstract: IMPORTANCEWomen in midlife often develop chronic conditions and experience declines in physical health and function. Identifying factors associated with declines in physical health and function among these women may allow for targeted interventions. OBJECTIVE To examine the factors associated with clinically important 10-year declines in the physical component summary score (PCS) of the Short Form 36 (SF-36), a widely used patientreported outcome measure, in women in midlife. DESIGN, SETTING, AND PARTICIPANTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…In fact, PCS was significantly negatively associated with smoking (beta = −2.286; p = 0.006), full-term pregnancy (beta = −2.513; p = 0.003), and comorbidities (beta = −5.035; p < 0.001). These results are similar to the findings from a recent cohort study among 1091 women that reported that currently smoking and comorbidities were factors associated with the decline in the PCS score of the Short Form 36 [66]. Another important finding of the study was the negative relation between PCS and alcohol consumption.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, PCS was significantly negatively associated with smoking (beta = −2.286; p = 0.006), full-term pregnancy (beta = −2.513; p = 0.003), and comorbidities (beta = −5.035; p < 0.001). These results are similar to the findings from a recent cohort study among 1091 women that reported that currently smoking and comorbidities were factors associated with the decline in the PCS score of the Short Form 36 [66]. Another important finding of the study was the negative relation between PCS and alcohol consumption.…”
Section: Discussionsupporting
confidence: 89%
“…Second, reproductive information was self-reported 18 years after enrollment, which might lead to misclassification of exposure status; however, ample evidence suggests that maternal recall of pregnancy-related events is reliable [34,35]. women's long-term health [12,13]. Fourth, we did not have information on BMI before the first pregnancy for all women.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our sample size was modest, and we did not have enough women with births at age ≤18 years ( n = 27) to analyze them in a separate category and conduct the appropriate sensitivity analyses. Despite this, considering age at first birth before age 23 years as the lowest category is informative because this period represents the average age at college graduation in the United States and an important milestone associated with women's long‐term health [12, 13]. Fourth, we did not have information on BMI before the first pregnancy for all women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Several studies have found that physical health and functional limitations commence during midlife for women and that these limitations persist throughout midlife and into late adulthood. 2 , 3 , 4 Furthermore, evidence suggests that these limitations or decreases in physical health and function are associated with chronic conditions that develop before or during midlife. 5 However, other work has shown the highly dynamic nature of functional status during midlife, 6 demonstrating that some women may improve their physical health and functioning during this time.…”
Section: Introductionmentioning
confidence: 99%